1997
DOI: 10.1128/cdli.4.2.185-188.1997
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antinuclear antibody testing methods: immunofluorescence assay versus enzyme immunoassay

Abstract: Performances of anti-nuclear antibody testing by immunofluorescence assay (ANA-IFA) and enzyme immunoassay (ANA-EIA) were compared in relation to patient diagnosis. A total of 467 patient serum samples were tested by ANA-IFA (Kallestad; Sanofi) and ANA-EIA (RADIAS; Bio-Rad), and their age, sex, diagnosis, disease status, and medications were obtained through chart review. Reference ranges were established by testing 98 healthy blood donor samples. Eighty-six samples came from patients with diffuse connective t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Many studies were conducted in different countries to detect the superior method for detection of ANA in systemic rheumatic diseases such as SLE, systemic sclerosis, JIA, and mixed connective tissue diseases 1,7,12–18 . In our study, ANA by IFA using HEp‐2 cell substrate was positive in 27 patients out of a total of 40 patients.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Many studies were conducted in different countries to detect the superior method for detection of ANA in systemic rheumatic diseases such as SLE, systemic sclerosis, JIA, and mixed connective tissue diseases 1,7,12–18 . In our study, ANA by IFA using HEp‐2 cell substrate was positive in 27 patients out of a total of 40 patients.…”
Section: Discussionmentioning
confidence: 57%
“…The study by Gniewek et al. 18 was done on a large study population with different rheumatological diseases and they did not show any result specifically on SLE. This may be the probable explanation of the different results in our study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…indirect immunofluorescent (IIF), enzyme-link immunosorbant assay (ELISA), immunodiffusion, or radioimmunoassay (RIA)], 3,11,12 as well as the experience of the technicians. [13][14][15] Although the ELISA method is used widely at present and has higher sensitivity, the IIF method using Crithidia luciliae as a substrate gives higher specificity results. [16][17][18] Therefore, the ELISA method should be used as a screening test for anti-dsDNA and positive results should be confirmed using the Crithidia luciliae IIF technique.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated limited sensitivity and specificity of IIFA on HEp‐2 cells, especially for anti‐RNP and anti‐Ro antibodies . Novel approaches to improving the sensitivity and specificity of the IIFA ANA test include both ‘knock‐in’ and ‘knockout’ gene technology, to improve the ability to detect anti‐SSA/Ro60 on HEp‐2 substrates or antibodies against dense fine speckles (DFS70), which still needs wider interlaboratory validation.…”
Section: Discussionmentioning
confidence: 99%